How to Make Infrastructure Climate Resilient - Miller, Alan; Swann, Stacy (International Finance Corporation, Washington, DC, 2018)
In emerging markets, climate change threatens infrastructure that is critical for development. Roads, airports, water systems, and power plants are vulnerable to weather changes. Severe storms and major droughts can disrupt economic activity. Because private companies and investors in emerging markets often manage infrastructure projects through public-private partnerships, they will now need to address climate change risks when planning and building these projects. The uncertainty of such risks has made incorporating them into project planning a challenge, but new tools and approaches, including insurance, are helping PPPs better respond to climate risks.